AN AGENT APPROACH FOR PROVIDING SECURITY IN DISTRIBUTED SYSTEMS - Kussul, Nataliya; Shelestov, Andriy; Skakun, Serhiy (International Journal of Computing, 2014)
In this paper an agent approach for providing security in distributed systems such as computer networks, Grid systems is presented. This approach envisages on-line and off-line monitoring in order to analyze users’ activity. The monitoring is done with the use of intelligent methods, namely neural networks.